Effects of different cytoplasmic chaperones on outer membrane solubility in Escherichia coli; rOMP25 modeling - Trabzonlu, Kubra; Arasoglu, Tulin (YILDIZ TECHNICAL UNIV, 2023)
In this study, for the first time in the literature, is investigated the effects of different chaper-ones on outer transmembrane membrane protein solubility by modeling the expression of the recombinant Omp25 outer membrane protein, which is one of the main antigens against brucellosis and known to form inclusion bodies in the cytoplasm.
Keywords: rOmp25; Brucellosis; Inclusion Body; Molecular Chaperones; Protein Expression; Purification; BRUCELLA-MELITENSIS; TRIGGER FACTOR; PROTEIN; EXPRESSION; ABORTUS; BINDING; MICE; Engineering